UK Diplomatic representation in Oman (1971)
Keywords: Relations – Oman – Royaume-Uni

Political relations between Oman and UK (1971)
This file relates to relations between the UK and Oman. It contains correspondence, briefs, and records of conversations concerning: The visit of the Sultan of Oman Qaboos Bin...
Keywords: Relations – Oman – Royaume-Uni

Political relations between Oman and UK (1971)
This file relates to relations between the UK and Oman, and in particular the replacement of D G Crawford as the Consul General in Muscat by D F Hawley. It includes...
Keywords: Relations – Oman – Royaume-Uni

Visit of Roy Mason, Secretary of State for Defence, to Oman and Saudi Arabia, 19-28 April 1975: briefs (1975)
f° 62-63: Sur Yahya Omar Baruni conseiller du Sultan introduit par Omar Baruni
Keywords: Relations – Oman – Royaume-Uni

Les premiers avions franco-britanniques Jaguar sont livrés en mars - Isnard, Jacques (Le Monde diplomatique, 1977)
Keywords: Relations – Oman – Royaume-Uni